Enterprise governance and management accounting from the viewpoint of feed forward control / Akira Nishimura - Nishimura, Akira (Accounting Research Institute, Faculty of Accountancy & UiTM Press, 2006)
In a growing market world-economy, in which the scope for financial mismanagement increases, enterprises need to strengthen their strategic risk management. Enterprise governance is not only a publicly regulated issue but also a matter of self-control, since it is closely related to conformance and performance (value creation). Therefore, enterprise governance should be studied from the viewpoint of proactive and preventive (feed forward) control rather than a reactive and reflective (feedback) viewpoint.